Irrigation research priorities for Nigeria: Proceedings of a National Seminar held at the University of Ilorin, Nigeria from 20 to 23 April, 1993 - Nwa, E.U.; Pradhan, P. (International Irrigation Management Institute, 1993)
The seminar highlights the problems facing irrigation development in Nigeria. The research priorities needed to solve them and the need to develop sustainable irrigation for the country are discussed. Unanimously adopted recommendations and action programs are: A. Irrigation research priorities: 1. Irrigation performance assessment; 2. Economic issues; 3. Technological issues; 4. Institutional framework for irrigation management; 5. Environmental issues; 6. Sociological issues. B. Framework for irrigation research and a pilot project. C. Irrigation research networking.